Gender and Health Justice: The Impact of Gender Disparities on Healthcare Access in Indonesia (Indonesian Health Justice Review, 2024)
Gender disparities in healthcare access pose significant challenges to health equity in Indonesia. This paper examines the intersection of gender and health justice, focusing on how women in both urban and rural areas experience barriers to healthcare access. Despite advances in healthcare policy, women, especially in rural regions, face unique challenges including cultural norms, limited reproductive health services, and gendered economic inequalities. The study employs a gender-sensitive approach, analyzing qualitative interviews with female healthcare recipients, healthcare providers, and community leaders. Findings show that women’s healthcare needs are often marginalized, particularly in rural areas where traditional gender roles restrict women’s autonomy and access to health services. The paper argues that addressing gender disparities in healthcare requires both policy reforms and community-level interventions, including improving women’s access to sexual and reproductive health services, increasing female healthcare workforce participation, and challenging gender norms that limit women’s healthcare decision-making.